Resource desiring machines: The production of settler colonial space, violence, and the making of a resource in the Athabasca tar sands. (October 2019) - Simpson, Michael
Abstract: This paper examines the historical processes that transformed tar sands bitumen in the Athabasca river basin into a natural resource of Canada. The discourse of the resource was first applied to bitumen during the second half of the nineteenth century as the settler colonial state dispatched geologists into the region to quantify, calculate, and measure its properties, and to speculate upon its potential economic applications. The re-storying of bitumen as a natural resource fostered a sense of resource nationalism among citizens of this newly formed state, who projected their fantasies of a settler colonial future upon the stored potentialities that the resource offered. In turn, this desire to secure resources on behalf of the Canadian nation served to consolidate the state's incursion into the Athabasca, enabling the spatial reorganization of the region in accordance with the settler resource imaginary. Drawing on Deleuze and Guattari, I suggest that we can think about this relationship between settler colonialism and the resource as a "resource desiring machine, " where both the subject and the object of desire are co-produced through the relationship of desire itself. Moreover, I argue that this can help us to rethink the relationship between resources and violence. Rather than asking how and when resources cause violence, I argue that violence is inherent to the very category of resource. Violence is the constitutive moment of resource-making, and sustaining the resource imaginary relies on the ongoing violence (threatened or actual) of political and economic institutions such as private property and the state.